2014
DOI: 10.5435/jaaos-22-03-193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Malnutrition in Orthopaedic Surgery

Abstract: Malnutrition can increase the risk of surgical site infection in both elective spine surgery and total joint arthroplasty. Obesity and diabetes are common comorbid conditions in patients who are malnourished. Despite the relatively high incidence of nutritional disorders among patients undergoing elective orthopaedic surgery, the evaluation and management of malnutrition is not generally well understood by practicing orthopaedic surgeons. Serologic parameters such as total lymphocyte count, albumin level, prea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
216
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(235 citation statements)
references
References 25 publications
13
216
0
6
Order By: Relevance
“…Benefits of TKA in populations at greater risk for complications are less well defined. Morbid obesity and malnutrition have been shown to be associated with increased perioperative complications after TKA [5,6,10,12,16,18,19,27,32]; however, some studies have not shown an increased risk of perioperative complications in patients who are morbidly obese [3,13,14,23,25]. In addition, patients with morbid obesity are more likely to be malnourished than patients who are not obese, raising the question whether morbid obesity, malnutrition, or both, are independently associated with increased perioperative complications [12].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Benefits of TKA in populations at greater risk for complications are less well defined. Morbid obesity and malnutrition have been shown to be associated with increased perioperative complications after TKA [5,6,10,12,16,18,19,27,32]; however, some studies have not shown an increased risk of perioperative complications in patients who are morbidly obese [3,13,14,23,25]. In addition, patients with morbid obesity are more likely to be malnourished than patients who are not obese, raising the question whether morbid obesity, malnutrition, or both, are independently associated with increased perioperative complications [12].…”
Section: Introductionmentioning
confidence: 89%
“…Morbid obesity and malnutrition are thought to be associated with more frequent perioperative complications in patients after TKA [5,6,10,12,31]. In addition, both often are considered modifiable risk factors, and some surgeons suggest that they should be corrected before elective TKA [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Of their malnourished cohort, however, 72.8% of patients had a normal albumin and low transferrin. While albumin, lymphocyte count, and transferrin are all useful markers of nutritional status [9], it is difficult to compare prevalence rates between studies with different definitions of malnutrition. However, despite varying definitions in the orthopedic literature, malnutrition has been associated with prosthetic joint infections as well as persistent wound drainage, hematoma formation, infection, renal complications, and cardiac complications postoperatively [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, orthopedic surgeons are becoming increasingly aware of the importance of nutritional status prior to elective surgery [9,18,22,27]. To define malnutrition, most surgeons use serum laboratory values such as albumin concentration and total lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…These include orthopaedics, abdominal surgery, head and neck surgery, neurosurgery, where poor nutritional status leads to a higher risk of infection, increased rate of failure of surgery or worsen the long-term outcome. The methods used for detecting patients at risk included serologic parameters, especially the use of prealbumin, clinical measurements, including hand-grip or nutritional risk scores (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%